A comprehensive analysis of vitamin a deficiency burden and trends: insights from the global burden of disease study 2021 and future predictions to 2050 - Hu, Qianhong; Lyu, Junying; Li, Jianying; Lin, Xiaoqing; Li, Sisi; Bu, Yiming; Zhao, Qianlei (Frontiers in Nutrition, 2025)
BackgroundVitamin A deficiency (VAD) continues to pose a significant public health challenge, particularly in low socio-demographic index (SDI) regions, contributing to increased infections, blindness, and child mortality. Its causes include poor diets, absorption issues, and infectious diseases.ObjectiveTo comprehensively assess the global trends and burden of Vitamin A Deficiency from 1990 to 2021 and to forecast the global VAD-related burden from 2022 to 2050.MethodsThis investigation employed data from the GBD 2021 database to analyze the global burden of nutritional deficiencies attributable to VAD. Disability-adjusted life-years (DALYs) and years lived with disability (YLDs) were systematically evaluated by gender, age groups, geographic regions, and countries over the 32-year study period (1990–2021). Temporal trends in age-standardized DALYs rate (ASDR) and age-standardized YLDs rate (ASYR) were quantified using estimated annual percentage change (EAPC) analysis. Projections of future burden were generated using exponential smoothing (ES) and autoregressive integrated moving average (ARIMA) models.ResultsIn 2021, the global burden of VAD was 1,104,931 DALYs, down from 1,970,337 in 1990. The ASDR dropped from 32.56 in 1990 to 15.73 in 2021, with an EAPC of −2.81%. Males had higher ASDR than females, both showing significant declines. The greatest burden was in the <5-year-old age group. An inverse SDI-ASDR associations was evident, with high-SDI regions achieving the fastest rate reductions. Projections to 2050 using ARIMA and ES models predicted a continued decrease in DALYs, with faster declines in males, although the ES model suggested a stabilization in DALYs for both genders.ConclusionThe GBD 2021 data underscored the persistent global challenge of addressing VAD. Solving this issue necessitates comprehensive strategies that combine targeted interventions, policy reforms, and collaborative efforts.